2003
DOI: 10.1124/jpet.103.053272
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Influences on Native T-Type Calcium Current in Thalamic Sleep Circuitry

Abstract: Ethanol is known to disrupt normal sleep rhythms; however, the cellular basis for this influence is unknown. This study uses an in vitro slice preparation coupled with electrophysiological recordings to probe neuronal responses to acute ethanol exposure. Recordings were conducted in ferret and rat thalamic slices, since thalamic circuitry is an integral component of sleep/wake cycles and sleep spindles. A key mediator of spindle wave activity is the low-threshold calcium current (T-type current). The T-type cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
(47 reference statements)
0
16
2
Order By: Relevance
“…Using monkeys treated like our CI group, a recent study (44) found plasticity in I T with chronic ethanol in the lateral geniculate nucleus (LGN). Although the direction of plasticity was opposite to our finding in the IO, low doses of ethanol augmented I T in LGN neurons (45), and the monkeys in that study (44) consumed less ethanol per day than did our CI group. The different outcomes could be caused by different Ca V 3.1 splice variants (46).…”
Section: Discussioncontrasting
confidence: 96%
“…Using monkeys treated like our CI group, a recent study (44) found plasticity in I T with chronic ethanol in the lateral geniculate nucleus (LGN). Although the direction of plasticity was opposite to our finding in the IO, low doses of ethanol augmented I T in LGN neurons (45), and the monkeys in that study (44) consumed less ethanol per day than did our CI group. The different outcomes could be caused by different Ca V 3.1 splice variants (46).…”
Section: Discussioncontrasting
confidence: 96%
“…In agreement with this suggestion, P-type channels were shown to be insensitive to EtOH concentrations as high as 200 mM in acutely dissociated rat cerebellar PNs (Hall et al, 1994;Walter and Messing, 1999). However, the effect of EtOH on T-type channel function in PNs has not been tested, and we cannot eliminate the possibility that EtOH modulates these channels in light of the recent demonstration that it potently regulates them in thalamic neurons (Mu et al, 2003). Voltage-clamp electrophysiological studies, which have faster temporal resolution than our Ca 2ϩ imaging studies, may reveal effects of ethanol on VGCCs in PNs.…”
Section: Etoh Does Not Affect the Camentioning
confidence: 55%
“…Our prior studies have shown significant effects of ethanol exposure and withdrawal on the physiology of T-type channels (Carden et al, 2006; Graef et al, 2011; Mu, Carden, Kurukulasuriya, Alexander, & Godwin, 2003; Shan, Hammarback, & Godwin, 2013; Wiggins, Graef, Huitt, & Godwin, 2013). Our current study extends these findings with the following observations: 1) ethanol withdrawal increased the incidence of seizure in DBA/2J mice; 2) ETX decreased ethanol withdrawal-induced seizures evident by reduced electrographical and behavioral measures of seizure; 3) ETX treatment rescued mice from seizures prior to withdrawal treatment.…”
Section: Discussionmentioning
confidence: 99%